The Impact of Agricultural Exports to China on the Pacific Alliance Economies: A Short- and Long-Run Analysis - Nadia Urriola Canchari, Theodore Murindahabi, Xiangzheng Deng (International Journal of Advanced Science and Technology, 2020)
This study aimed to analyze and quantify the short and long-run impact of agricultural exports to China on the economic growth of the Pacific Alliance’s Economies in the period from 2001 to 2018. Agricultural exports to China (AXCH), the labor force (LF), and foreign direct investment (FDI) values were used as determinant factors of economic growth. The study employed Vector Autoregression (VAR) Model, Johansen Co-integration test, and Granger Causality test for data analysis. The results showed that, in the short run, the economic growth and AXCH have a positive effect on the economic growth of Pacific Alliance’s Economies. At the same time, both FDI and LF have a positive impact on the GDP. Moreover, the Co-integration test result revealed a long-run relationship between the studied variables, and a causality relationship between the economic growth and the AXCH, the FDI and the LF. Finally, we observed that the impact on the Pacific Alliance’s Economies is bigger than the impact in each member country. The study suggests some recommendations to improve the agriculture sector’s performance as a driver of sustainable economic growth in the region.